Do They Get Close? Party Shifts and Changes in Parliamentary Congruence on Multiple Issue Dimensions in the Wake of the Crises - Mirjam Dageförde (Representation, 2024)
This article explores congruence in the wake of the crises. It analyses (1) shifts in parties' positions on multiple issue dimensions and (2) examines congruence between citizens and parliament in times of crisis. The article refers to three issue dimensions: left-right, migration and European integration. First, I hypothesise that shifts in party positions are more pronounced on newly contested issue dimensions, such as migration or European integration, than on the left-right dimension. Second, I argue that systemic congruence will increase over the course of time. Third, I posit that systemic congruence will increase particularly on newly contested issue dimensions, like migration and European integration. The study brings together a set of Western European countries: France, Germany, Great Britain, Spain and Sweden. The analysis is based on CHES- and ESS-data (2006–2018/2019) and explores congruence as a many-to-many relationship. In large part, the results confirm the hypotheses. First, party positions changed, and shifted particularly on the issue dimensions of European integration and migration. Second, systemic congruence increased in several cases. Third, the most profound changes are to be found on the issue dimension of European integration.
Keywords: 320; representation; congruence; parties; citizens/voters; parliament